A propos des "transitions démocratiques" notes comparatives et préalables à l’analyse du cas angolais - Messiant, Christine (Africana Studia, 2020)
This article studies the problem of the so-called African "democratic transitions", revisiting under a cri ti cal point of view the case of Angola,. A substantial part of this study lies in the intersection between the notion of the politica! economy and the contextual sociological dimension of the studied issues.